Constructing an analysis method for urban collective identities - Nápoles Franco, Diego (Centro Universitario de Arte, Arquitectura y Diseño, 2020)
Despite the movement of collective identities, societies maintain cultural elements linked to belonging and, in general, to their own characte-rization as collectives and individuals. In cities, identities deserve an analysis focused not only on the urban scaffolding but in a much more complex structure that delves into the daily collective life of the modern world. It is in this sense that ethnographic research proposes new methodolo-gical approaches for the treatment of identities, especially in the continuous socio-spatial reconfigurations where the inhabitants construct particular perceptions of the city, but at the same time shared and replicated in a spatial and temporal period. More dynamic than ever. The proposal focuses not only on conceptual development but also on the methodological structuring through elements such as: categories, indicators, obser-vables, sources and tools with which urban sociology can be treated. Consequently, the work leads to retake dimensional aspects of the object of study proposing a common scenario, which could undoubtedly be adjusted according to certain contexts and potential characteristics of urbanizations. The purpose of the presentation is directed towards a continuous collaboration on the structural contents of the methodological treatment for collective identities, taking theoretical references of the collective identity as cons- tructions that de ne societies with respect to others and that at the same time nd a variation between their agglomerates (Giménez, 2008).